Using ICT for education and sustainable development among the underserved in Africa - Kwapong, T.F.O.A. (Journal on School Educational Technology 5(1): 56 – 67, 2009)
The potential of ICT for education and sustainable development cannot be underestimated. Using cases from some African countries and data from deprived regions in Ghana, this paper discusses the opportunities and challenges in ICT for education and sustainable development in underserved areas in Africa. Much as infrastructural development, illiteracy and financial bottlenecks limits the possibility of fully utilizing emerging technologies, the growth of innovative technology like mobile telephony presents opportunities for using ICT to kick out of poverty through education. In this process the concern should not just be to provide access but to implement development programs that will meet the educational, agricultural, economic and healthcare needs of the people in underserved areas.
Keywords: Information; communication; technology; education; development; Africa; Internet